2017
DOI: 10.1177/1403494817701566
|View full text |Cite
|
Sign up to set email alerts
|

Spatial social polarization and birth outcomes: preterm birth and infant mortality – New York City, 2010–14

Abstract: These results provide preliminary evidence for the use of the ICE measure in examining structural barriers to healthy birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 53 publications
4
39
1
10
Order By: Relevance
“…A growing body of literature has examined the relationship between structural racism and adverse birth outcomes (Ahern, Pickett, Selvin, & Abrams, 2003;Chambers, Baer, McLemore, & Jelliffe-Pawlowski, 2018;Chambers, Erausquin, Tanner, Nichols, & Brown-Jeffy, 2017;Farley et al, 2006;Huynh et al, 2017;Huynh, Parker, Harper, Pamuk, & Schoendorf, 2005;Kaufman, Dole, Savitz, & Herring, 2003;Krieger et al, 2017;Mendez, Hogan, & Culhane, 2011;Messer, Kaufman, Dole, Savitz, & Laraia, 2006;O'Campo et al, 2008;Woodward, 1995). Structural racism is defined as a systematic approach used to influence laws and process to unequally allocate access to goods, opportunities, and services in society by racial group (Bailey et al, 2017;Gee & Ford, 2011;Jones, 2001;Massey & Denton, 1988;Mehra, Boyd, & Ickovics, 2017;Ncube, Enquobahrie, Albert, Herrick, & Burke, 2016;White & Borrell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has examined the relationship between structural racism and adverse birth outcomes (Ahern, Pickett, Selvin, & Abrams, 2003;Chambers, Baer, McLemore, & Jelliffe-Pawlowski, 2018;Chambers, Erausquin, Tanner, Nichols, & Brown-Jeffy, 2017;Farley et al, 2006;Huynh et al, 2017;Huynh, Parker, Harper, Pamuk, & Schoendorf, 2005;Kaufman, Dole, Savitz, & Herring, 2003;Krieger et al, 2017;Mendez, Hogan, & Culhane, 2011;Messer, Kaufman, Dole, Savitz, & Laraia, 2006;O'Campo et al, 2008;Woodward, 1995). Structural racism is defined as a systematic approach used to influence laws and process to unequally allocate access to goods, opportunities, and services in society by racial group (Bailey et al, 2017;Gee & Ford, 2011;Jones, 2001;Massey & Denton, 1988;Mehra, Boyd, & Ickovics, 2017;Ncube, Enquobahrie, Albert, Herrick, & Burke, 2016;White & Borrell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ICE measures have been used across a number of health outcomes, such as analyses examining stress, breast cancer, infant and diabetes mortality, airborne pollutants, hypertension, violence, and preterm births (Feldman et al, ; Finch et al, ; Huynh et al, ; Krieger et al, ; Krieger et al, ; Krieger, Feldman, Kim, & Waterman, ; Krieger, Singh, & Waterman, ; Krieger, Waterman, Gryparis, & Coull, ). The previous investigations into how concentrated neighborhood disadvantage affects health utilized the ICE in relation to economic measures, such as household income, and found that individuals have increasing gradations of poor health outcomes when such factors have been examined using the ICE (Krieger, Singh, & Waterman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, residential segregation is a broad concept that refers to housing separated from different population groups in different parts of a city [18]. Segregation affects health by intensifying psychosocial effects involving insecurity, anxiety, social isolation, socially dangerous environments, bullying, and depression [14,19,20]. In our analysis, we considered two aspects of segregation: education and income, including levels of income stratified by ethnic groups, which better describe socioeconomic differences in Brazil.…”
Section: Socioeconomic Variables and Dimensions Of Contextmentioning
confidence: 99%